Development of Gamified Scrapbook Teaching Media to Improve Ecoliteracy of Fifth Grade Elementary School Students - Putri Ayu; Suratmi Suratmi; Laihat Laihat (Universitas Sriwijaya, 2026)
ABSTRACT This study aimed to develop gamified scrapbook teaching media to improve the ecoliteracy of fifth grade elementary school students at SDN 72 Palembang using the ADDIE development model. The research focused on analyzing the feasibility, practicality, and effectiveness of the developed media. The results showed that material expert validation reached 90.62% (very feasible), media expert validation 97.22% (very feasible), and practitioner validation 98.3% (very practical). Student responses at the individual stage obtained 95.83% (very practical) and at the small group stage 93.21% (very practical). Furthermore, the N-Gain score was 0.828 in the very high category. These findings indicate that gamified scrapbook teaching media is valid, practical, and effective to be applied in learning activities to enhance students’ ecoliteracy.